Answer:
Neither expression satisfies the given rational root.
Explanation:
To find the right answer, we just need to replace the given root in each expression and see which one gives zero.
First expression.
![f(x)=4x^(4) -7x^(2) +x+25\\f(-(2)/(5))= 4(-(2)/(5))^(4) -7(-(2)/(5))^(2) +(-(2)/(5))+25=(64)/(625)-(28)/(25) -(2)/(5) +25 \approx 23.58](https://img.qammunity.org/2021/formulas/mathematics/college/r9630gbqqlaqft5ryjbry1e2ql7nehpxmd.png)
Second expression.
![f(x)=9x^(4)-7x^(2) +x+10=9(-(2)/(5) )^(4) -7(-(2)/(5) )^(2) +(2)/(5) +10 \approx 9.5](https://img.qammunity.org/2021/formulas/mathematics/college/nuuc7oh9i3rvwhq83m20ach6j9zvpo1gj3.png)
Third expression.
![f(x)=10x^(4)-7x^(2) +x+9=10(-(2)/(5) )^(4) -7(-(2)/(5))^(2) +(-(2)/(5))+9 \approx 7.7](https://img.qammunity.org/2021/formulas/mathematics/college/dpsvzsp8p3ahyad5aqkfw532lbftq7ntnz.png)
Fourth expression.
![f(x)=25x^(4)-7x^(2) +x+4=25(-(2)/(5) )^(4) -7(-(2)/(5))^(2) +(-(2)/(5))+4 \approx 3.12](https://img.qammunity.org/2021/formulas/mathematics/college/tpvbq1chwp3nugwgl71g8tj5yja2zvv8y6.png)
Therefore, neither expression satisfies the given rational root.